Prospective, historically controlled study to evaluate the efficacy and safety of a new paediatric formulation of nifurtimox in children aged 0 to 17 years with Chagas disease one year after treatment (CHICO). - Jaime Altcheh; Luis Castro; Juan C Dib; Ulrike Grossmann; Erya Huang; Guillermo Moscatelli; Jimy José Pinto Rocha; Teresa Estela Ramírez; CHICO Study Group (Public Library of Science (PLoS), 2021)
Nifurtimox is a recommended treatment for Chagas disease, but data from treated children are limited. We investigated the efficacy, safety and tolerability of nifurtimox administered as divisible, dispersible 30 mg and 120 mg tablets in children with Chagas disease. In this blinded, controlled study conducted January 2016-July 2018, 330 patients aged <18 years from 25 medical centres across three South American countries were randomised 2:1 to nifurtimox 10-20 mg/kg/day (aged <12 years) or 8-10 mg/kg/day (aged ≥12 years) for 60 days (n = 219), or for 30 days plus placebo for 30 days (n = 111) (ClinicalTrials.gov NCT02625974). The primary outcome was anti-Trypanosoma cruzi serological response (negative seroconversion or seroreduction ≥20% in mean optical density from baseline determined by two conventional enzyme-linked immunosorbent assays) at 12 months in the 60-day treatment group versus historical placebo controls. Nifurtimox for 60 days achieved negative seroconversion (n = 10) and seroreduction (n = 62) in 72 patients (serological response 32.9%; 95% confidence interval [CI] 26.4%, 39.3%, of all treated patients), confirming superiority relative to the upper 95% CI of 16% for controls. In patients aged <8 months, 10/12 treated for 60 days (83.3%) and 5/7 treated for 30 days (71.4%) achieved negative seroconversion. Overall serological response was lower for 30-day than for 60-day nifurtimox (between-treatment difference 14.0% [95% CI 3.7%, 24.2%]). The frequency of T. cruzi-positive quantitative polymerase chain reactions decreased substantially from baseline levels (60-day regimen 53.4% versus 1.4%; 30-day regimen 51.4% versus 4.5%). Study drug-related treatment-emergent adverse events (TEAEs), which were observed in 62 patients (28.3%) treated for 60 days and 29 patients (26.1%) treated for 30 days, were generally mild or moderate and resolved without sequelae; 4.2% of all TEAEs led to nifurtimox discontinuation. Age- and weight-adjusted nifurtimox for 60 days achieved a serological response at 12 months post-treatment that was superior to historical placebo, was well tolerated and had a favourable safety profile in children with Chagas disease. Although, at 1 year serological follow-up, efficacy of the shorter nifurtimox treatment was not comparable to the 60-day treatment regimen for the overall study population, further long-term follow-up of the patients will provide important information about the progress of serological conversion in children treated with nifurtimox, as well as the potential efficacy difference between the two regimens over time.